Pitfall in Ultrasound Evaluation of Uterine Scar from Prior Preterm Cesarean Section - Sarah-Maude B. Laflamme; Nicole Jastrow; Mario Girard; Gaétan Paris; Laurie Bérubé; Emmanuel Bujold (Thieme Medical Publishers, Inc., 2011)
We report two cases of women with a previous cesarean performed before active labor at 29 weeks of gestation who underwent sonographic measurement of the lower uterine segment (LUS) at 36 weeks' gestation in their subsequent pregnancy. In both cases, uterine scar defect was detected on the upper part of the LUS, at ~9 to 11 cm from the cervical os, and was only visualized by the transabdominal approach. We suggest that early gestational age and the absence of labor at previous cesarean can lead to a higher uterine scar location on the LUS and, therefore, increase the risk of uterine rupture in subsequent pregnancy. The heterogeneity of uterine scar location could explain discrepancies observed in studies using the transabdominal versus the transvaginal approach or both regarding the predictive value of LUS measurements for uterine rupture.